Evaluating the right to life: Lessons from Nigeria, the African Charter, and Indonesian regulations - Uche Nnawulezi; Okibe Emmanuel; Suhadi Suhadi; Salim Bashir Magashi; Septhian Eka Adiyatma (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: The problem of the study is basically on exploring the inadequacies of the existing regulations in safeguarding human life as continuous violations of the sanctity of human dignity have remained unabated in recent years in Nigeria. Purpose/Study Objectives: The purpose of the study is to examine the phenomenon of the right to life in CFRN, 1999 and ACHPR,1981 and their contributions to the fundamental rights enforcement system. Drawing on past or present human rights abuses of the constitutional rights of individuals in Nigeria, the question asked is whether human rights instruments in place are no longer capable of adequate protection of human life in Nigeria. In this sense, the aims of the study are to understand this issue by examining the strengths and weaknesses of the legal frameworks meant to protect lives in Nigeria. The paper argued that the CFRN 1999 and ACHPR 1981 have an absolute prohibition on abuse of human life. The paper examines, among others, the obligations on states to adopt measures capable of addressing the incessant abuse of human rights. Comparing Indonesia as a comparative country in noticing and comparing a country with a different culture. Design/Methodology/Approach: This study uses an analytical and qualitative approach to the current legislation, policies and literature on constitutional rights and this is achieved by synthesizing ideas and comparing with the rules of other countries, especially Indonesia. Findings: The research found that lack of prosecution, political interference, and insufficient accountability hinder human rights enforcement in Nigeria. Despite this, the CFRN 1999 and ACHPR 1981 can still protect lives if human rights legislation is reformed to be more proactive. The comparison with Indonesia highlights that each country has unique customs and characteristics in safeguarding the right to life. Paper Type: Research Article